Exosomes: potential diagnostic markers and drug carriers for adenomyosis - Cheng, Wen-Xiu; Wei, Shao-Bin; Zhou, Yang; Shao, Yu; Li, Mao-Ya (Frontiers in Pharmacology, 2023)
Adenomyosis is a common benign gynecological disorder and an important factor leading to infertility in fertile women. Adenomyosis can cause deep lesions and is persistent and refractory in nature due to its tumor-like biological characteristics, such as the ability to implant, adhere, and invade. The pathogenesis of adenomyosis is currently unclear. Therefore, new therapeutic approaches are urgently required. Exosomes are nanoscale vesicles secreted by cells that carry proteins, genetic materials and other biologically active components. Exosomes play an important role in maintaining tissue homeostasis and regulating immune responses and metabolism. A growing body of work has shown that exosomes and their contents are key to the development and progression of adenomyosis. This review discusses the current research progress, future prospects and challenges in this emerging therapeutic tool by providing an overview of the changes in the adenomyosis uterine microenvironment and the biogenesis and functions of exosomes, with particular emphasis on the role of exosomes and their contents in the regulation of cell migration, proliferation, fibrosis formation, neovascularization, and inflammatory responses in adenomyosis.